Research advances in evaluation methods for neoadjuvant therapy of tumors - Yuan, Zien; Chen, Ting; Zhang, He; Li, Jiatong; Li, Juntan; Shang, Guanning (Frontiers in Oncology, 2025)
Preoperative neoadjuvant therapy is crucial for large malignant tumors or tumors that are challenging to resect. Consequently, an objective assessment of its therapeutic efficacy is important. Currently, the conventional evaluation methods for neoadjuvant therapy of tumors are mainly divided into two categories: imaging-based and pathological evaluations. In imaging-based evaluation, the World Health Organization criteria are straightforward; however, they exhibit some issues such as unclear criteria for minimum lesions and measurement errors. Moreover, although the Response Evaluation Criteria In Solid Tumors criteria have been improved, they remain insensitive to internal tumor changes and are prone to measurement errors. The Modified Response Evaluation Criteria In Solid Tumors criteria are specifically designed for hepatocellular carcinoma, yet they have limitations, such as difficulty defining complex tumor boundaries. The Positron Emission Tomography Response Criteria in Solid Tumors criteria, which integrate positron emission tomography/computed tomography, offer high accuracy but are influenced by factors related to the patient’s body condition and equipment. The Choi criteria, which comprehensively consider tumor size and density, can be used to evaluate the efficacy of targeted therapy; however, they are characterized by cumbersome measurement procedures and strong subjectivity. In terms of pathological evaluation, the Huvos score determines the therapeutic effect based on the degree of tumor necrosis, which can guide subsequent treatment and prognosis. However, the evaluation time is fixed and subject to interference from pathological procedures. The Miller–Payne criteria focus on changes in the number and density of tumor cells and provide a reference for surgical decision-making. Nevertheless, it does not consider lymph node metastasis. The Residual Cancer Burden assessment criteria comprehensively quantify residual tumors by integrating multiple factors. Moreover, these offer a precise assessment of breast cancer and have a high value in predicting prognosis. However, their parameter calculation is complex and highly subjective. In summary, each method has its own advantages and disadvantages. With the advancement of scientific research, evaluation methods for neoadjuvant therapy are constantly evolving. In-depth research into these methods can help identify more accurate and effective evaluation strategies, providing a more scientific basis for tumor treatment and propelling the field of tumor therapy toward greater precision.